Sampling a vortex from a Gaussian beam using a wedge-plate shearing interferometer - Kerridge-Johns,WR; Jaillot,J-B; Damzen,MJ (Applied Optics, 2021)
Many vortex-generation techniques have been developed to address a range of potential applications, exploiting their unique amplitude and phase profiles and their possession of orbital angular momentum. In this work, we present what may be the simplest method of vortex beam generation, requiring only a wedged optic: the wedge-plate shearing interferometer (WPSI). We show that the WPSI can reflect a first order Laguerre–Gaussian vortex beam (LG01) with a theoretical purity of >99% from an input fundamental Gaussian beam, with 98% LG01 purity experimentally demonstrated. We demonstrate 1% power conversion with a route to 14%. The monolithic WPSI is a simple, compact, and highly stable device, which can operate at any wavelength that the material is transparent to. We anticipate that it will be useful where sampling a robust, high-purity vortex beam from a Gaussian laser beam is required, including low-cost vortex generation for metrology or education.